Coconut Water Based Extender Effects on Motility,Viability, and DNA Integrity of Chilled Kintamani Dog Semen - I Wayan Nico Fajar Gunawan; I Made Kardena; I Ketut Suatha; I Ketut Puja (Veterinary Science and Medicine Journal, 2016)
This research was conducted to investigate coconut water based extenders as an alternative extender for chilled Kintamani dog semen. Semen were collected from five dogs using manual stimulation and evaluated microscopically. Sperm were stored at 50C and divided into two aliquots which were extended with either coconut water based extender and sodium citrate extender in the ratio 1:2, 1:3 and 1:4. Sperm motility, viability and DNA integrity immediately and periodically (0,3 and 6 hour) were evaluated. Result showed that the effect of diluent on sperm motility and integrity of the Kintamani dog exerted a highly significant (p<0.01), whereas it had no effect on the percentage of dead sperm (p> 0.05). These results indicate that coconut water extender give good results in maintaining the motility, viability and DNA integrityof Kintamani dog sperm. It is concluded that coconut water suitable for extender of Kintamani dog.